Personal qualities of effective sport psychologists: coping with organisational demands in high performance sport - Chandler, C.; Eubank, M.; Nesti, M.; Tod, D.; Cable, T. (International Journal of Sport Psychology, 2016)
The purpose of the current study was to explore colleagues' perspectives of the personal qualities of effective sport psychologists and how these qualities enable practitioners to address the organisational demands they face within their work. Semi-structured interviews were conducted with sport physicians (N = 6) and coaches (N = 7). Data analysis identified three main themes: understanding high performance sport environments and cultures, the wider organisational role in high performance sport, and working with support staff in high performance sport. This study provides insight into the wider organisational role of sport psychology in high performance sport and the personal qualities that are fundamental to effective service delivery in this environment. Suggestions are offered regarding how education and training could better prepare practitioners for addressing organisational demands within their role, by developing trainees' awareness of their personal qualities and providing them with the opportunity to critically explore these qualities in the context of applied sport psychology practice.